Use your words: The role of emotion labeling in regulating emotion in borderline personality disorder. (September 2019) - Fitzpatrick, Skye; Ip, Jennifer; Krantz, Lillian; Zeifman, Richard; Kuo, Janice R.
Abstract: Borderline personality disorder (BPD) treatments emphasize emotion labeling to decrease negative emotion and facilitate emotion regulation. However, no studies have examined emotion labeling in BPD or its impact on intentional emotion regulation. The present study examined the impact of emotion labeling on emotion and intentional emotion regulation attempts across self-reported and physiological indices (i.e., skin conductance response [SCR], respiratory sinus arrhythmia [RSA]) in BPD and healthy control (HC) groups. Participants listened to emotionally-evocative scripts and were either instructed to type the emotions that they were experiencing (labeling) or the objects they could imagine seeing in the script (control) into a computer. Following this, they were instructed to use either mindfulness or cognitive reappraisal to decrease their emotion. Self-reported, RSA, and SCR indices of negative emotion were collected throughout and analyzed using generalized estimating equations. Findings indicated that the BPD group experienced higher RSA during emotion labeling compared to the control task, but the HC group did not. HCs reported lower negative emotion after emotion labeling when implementing both emotion regulation strategies compared to the control task, but the BPD group did not. These findings suggest that emotion labeling may activate emotion regulatory systems in BPD and can potentiate intentional emotion regulation in HCs. Highlights: Examined emotion labeling in borderline personality disorder (BPD). Studied its impact on emotion and emotion regulation in BPD, healthy controls (HCs). Labeling decreased physiological distress per respiratory sinus arrhythmia in BPD. Labeling improved intentional self-reported emotion regulation in HCs. Labeling may be important to regulate some domains of emotion in BPD.